(3GdJbGQjQ GdEYdGejI (B/s - (3QRGbj, YHO GdYGdj s ((3GdLRGFQ (B:s (3OGQ GdCeI ddfTQ h GdJhRjY ,s, 2014)
(3h gG gh GdLRA GdKGdK jJYeb aj GdcJGHGJ GdGSJSbGFjI Gh eGjSeG HGdcJGHI GdJbQjQjI h JTed GdJbGQjQ cfhY UMaj h GeJOGOg aj GdMOjK GdGYdGej h GdJMbjb h GdQhHhQJGL h GdUhQI GdbdejI h gPg GdGfhGY GdGYdGejI JJbGWY ajeG HjfgG HGYJHGQgG Yed ejOGfj jdLG Gdi GdJMQj Ih GdJbUj h GdGSJYdGe HGdGJUGd GdeHGTQ eY GdMOK Gh GdeYdheI Gh GdQGj h ef NdGd bQGAJj GdeJhGVYI dcKjQ eeG cJH Mhd afjGJ GdJMQjQ h JbfjGJ GdcJGHI GdGYdGejI NdUJ Gdi Gf GdcKjQ ef GdOQGSHf dgPg GdGfhGY de Jcf dge NHQI ejOGejI cGajI aGNJdWJ Ydjge GdGfhGY GdZYdGejI h JOGNdJ eaGgjegG dOjge aGWfHhG aj GdJfXjQ h eGTOfj GcKQ Gf GdcJGHI GdUMajI gj GfgG eG JRGd SGFOI aj GdHMhK GdGYdGejI h gh jYfj Gf GdOQGSG GdeQJHWI HGdcJGHI ddejcQhahf Gh GdUhQI Gh GdUhJ Gh GdUMGaI GdGdcJQhfjI JcGO Ge Jchf fGOQI QHeG dGf GdejOGf GdSeYj GdHUQj eGjRGd jSJNOe dZI efJLj GLgRI h GdGJgs
(3HjHdjhZQGajG(B:(3U(B.168-176s
Keywords: (3GdJbGQjQ GdEYdGejIs; (3GdcJGHI GdJbQjQjIs; (3GdcJGHI GdUMajIs